2017
DOI: 10.29333/ajqr/5788
|View full text |Cite
|
Sign up to set email alerts
|

Disability or Language Difference: How Do We Decide?

Abstract: Increased globalization has resulted in increased attendance of language minority students in schools worldwide. These language differences confound efforts to identify students with disabilities. This case study provides a hypothetical example of interaction between language, social, and academic difficulties in determining existence of a disability and planning appropriate academic programming for a recently immigrated elementary school student named Filipe. Users of this case must analyze and synthesize cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Pokazalo se da ukoliko roditelji imaju prezaštićujući stav prema svom detetu, oni se odnose prema svojoj deci kao da, na neki način, ne odrastaju, već da su i dalje bebe koje su zavisne od njihove brige i nege (Takako, 1994, prema Yilmaz & Tolan, 2021. Postoje empirijski nalazi koji ukazuju na to da deca koja odrastaju uz roditelje koji su previše zaštitnički nastrojeni, to može delovati na decu tako da imaju subjektivni doživljaj da nisu sposobna da donesu odluke lične prirode i da nisu dovoljno kompetentna u interpersonalnim relacijama (Carothers & Parfitt, 2017).…”
Section: Vaspitni Stavovi Roditeljaunclassified
“…Pokazalo se da ukoliko roditelji imaju prezaštićujući stav prema svom detetu, oni se odnose prema svojoj deci kao da, na neki način, ne odrastaju, već da su i dalje bebe koje su zavisne od njihove brige i nege (Takako, 1994, prema Yilmaz & Tolan, 2021. Postoje empirijski nalazi koji ukazuju na to da deca koja odrastaju uz roditelje koji su previše zaštitnički nastrojeni, to može delovati na decu tako da imaju subjektivni doživljaj da nisu sposobna da donesu odluke lične prirode i da nisu dovoljno kompetentna u interpersonalnim relacijama (Carothers & Parfitt, 2017).…”
Section: Vaspitni Stavovi Roditeljaunclassified
“…Ethnicity is generally defined as a group with similarities in terms of geography, religion, sect, descent, language, cultural norms, and traditions (Carothers & Parfitt, 2017;Dinnerstein, 1991;Horowitz, 1985Horowitz, , 2011Smedley, 1993;Varshney, 2008). Aspinall (2020) argued that the term ethnicity is "representation" because it depends on who interprets its ethnicity.…”
Section: Ethnic Minoritiesmentioning
confidence: 99%
“…In fact, suggested that not only is the impact of headache in adolescents significant, but that the impact remains unrecognized and often goes unaddressed. Fuh and colleagues (2010), Carothers and Parfitt (2017) found that adolescents aged 13-15 with migraine reported significantly higher levels of disability than their peers with tension-type headache.…”
Section: Disabilitymentioning
confidence: 99%